Outcomes and Outcome Measures in Breast Reduction Mammaplasty: A Systematic Review. (4th November 2019) - Waltho, Daniel; Gallo, Lucas; Gallo, Matteo; Murphy, Jessica; Copeland, Andrea; Mowakket, Sadek; Moltaji, Syena; Baxter, Charmaine; Karpinski, Marta; Thoma, Achilleas
Abstract: Background: Reduction mammaplasty remains critical to the treatment of breast hypertrophy. No technique has been shown to be superior; however, comparison between studies is difficult due to variation in outcome reporting. Objectives: The authors sought to identify a comprehensive list of outcomes and outcome measures in reduction mammaplasty. Methods: A comprehensive computerized search was performed. Included studies were randomized or nonrandomized controlled trials involving at least 100 cases of female breast hypertrophy and patients of all ages who underwent 1 or more defined reduction mammaplasty technique. Outcomes and outcome measures were extracted and tabulated. Results: A total 106 articles were eligible for inclusion; 57 unique outcomes and 16 outcome measures were identified. Frequency of patient-reported and author-reported outcomes were 44% and 88%, respectively. Postoperative complications were the most frequently reported outcome (82.2%). Quality-of-life outcomes were accounted for in 37.7% of studies. Outcome measures were either condition-specific or generic; frequencies were as low as 1% and as high as 5.6%. Five scales were formally assessed in the breast reduction populations. Clinical measures were defined in 15.1% of studies. Conclusions: There is marked heterogeneity in reporting of outcomes and outcome measures in the literature. A standardized outcome set is needed to compare outcomes of various reduction mammaplasty techniques. Level of Evidence: 4: